HUBUNGANÂ KELEKATANÂ DENGANÂ KECERDASANÂ EMOSIÂ DANÂ PENYESUAIANÂ SOSIALPADAÂ ANAKÂ USIAÂ DINIÂ - henni anggraini; sarah emmanuel (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
AttachmentÂ  isÂ  isÂ  theÂ  tendencyÂ  andÂ  desireÂ  ofÂ  anÂ  individualÂ  isÂ  aÂ  childÂ  toÂ  seekÂ  proximity withÂ  theirÂ  guardiansÂ  (MonkÂ  etÂ  all,Â  2004).ThereÂ  areÂ  fourÂ  basicÂ  principlesÂ  ofÂ  theÂ  bond betweenÂ  parentÂ  andÂ  childÂ  isÂ  the physicalÂ  needsÂ  ofÂ  childrenÂ  forÂ  foodÂ  andÂ  warmthÂ  thatÂ  filled byÂ  theirÂ  mother,Â  theÂ  encouragementÂ  ofÂ  originÂ  whichÂ  isÂ  ownedÂ  byÂ  theÂ  childÂ  toÂ  clingÂ  toÂ  the mother'sÂ  chest,Â  theÂ  babyÂ  neededÂ  toÂ  touchÂ  andÂ  clungÂ  byÂ  aÂ  person,Â  andÂ  theÂ  disappointment ofÂ theÂ babyÂ asÂ itÂ isÂ expelledÂ fromÂ inÂ theÂ wombÂ (Bowlby,Â 1969).Â TheÂ qualityÂ ofÂ aÂ relationship betweenÂ  aÂ  childrenÂ  andÂ  aÂ  parentsÂ  areÂ  anÂ  importantÂ  factorÂ  forÂ  developmentÂ  ofÂ  children. TheÂ  theoryÂ  ofÂ  attachmentÂ  explainedÂ  thatÂ  childrenÂ  needÂ  attachmentÂ  withÂ  atÂ  leastÂ  one caregiverÂ  toÂ  developÂ  emotionalÂ  andÂ  socialÂ  development.Â  ThisÂ  studyÂ  aimsÂ  toÂ  determineÂ  the relationship betweenÂ  attachmentÂ  ofÂ  emotionalÂ  intelligenceÂ  andÂ  socialÂ  adjustmentÂ  inÂ  early childhood.Â  ThisÂ  studyÂ  usedÂ  quantitativeÂ  methodsÂ  toÂ  theÂ  subjectÂ  35Â  studentsÂ  ofÂ  classÂ  BÂ  TK muslimatÂ  NUÂ  22Â  agedÂ  5â€7Â  years.Â  TheÂ  collectingÂ  ofÂ  dataÂ  obtainedÂ  throughÂ  aÂ  scaleÂ  of attachmentÂ  betweenÂ  aÂ  childÂ  andÂ  aÂ  parents,Â  theÂ  scaleÂ  ofÂ  emotionalÂ  intelligenceÂ  andÂ  social adjustment.Â  Furthermore,Â  theÂ  dataÂ  wereÂ  analyzedÂ  byÂ  usingÂ  ProductÂ  MomentÂ  Pearson correlationÂ  analysisÂ  usingÂ  SPSSÂ  21.0Â  forÂ  windows.Â  TheÂ  resultÂ  showedÂ  thatÂ  thereÂ  wasÂ  a positiveÂ  andÂ  significantÂ  relationshipÂ  betweenÂ  attachmentÂ  withÂ  emotionalÂ  intelligenceÂ  and socialÂ adjustmentÂ inÂ earlyÂ childhoodÂ (rxy1Â =Â 0,537;Â rxy2=Â 0,513;Â pÂ =Â 0,005Â <Â 0,05).